Seasonal and spatial variability of CO 2 in aquatic environments of the central lowland Amazon basin - Amaral, João Henrique Fernandes; Farjalla, Vinícius Fortes; Melack, John M.; Kasper, Daniele; Scofield, Vinicius; Barbosa, Pedro Maia; Forsberg, Bruce Rider (Biogeochemistry, 2019)
Different sources and processes contribute to pCO 2 and CO 2 exchange with the atmosphere in the rivers and floodplains of the Amazon basin. We measured or estimated pCO 2 , CO 2 fluxes with the atmosphere, planktonic community respiration (PCR), and environmental and landscape variables along the Negro and Amazon-Solimões rivers during different periods of the fluvial hydrological cycle. Values of pCO 2 ranged from 307 to 7527 μatm, while CO 2 fluxes ranged from − 9.3 to 1128 mmol m −2 d −1 in the Amazon-Solimões basin. In the Negro basin, pCO 2 values ranged from 648 to 6526 μatm, and CO 2 fluxes from 35 to 1025 mmol m −2 d −1 . In a general linear model including data from Negro and Amazon-Solimões basins, seasonal and spatial variation in flooded vegetated habitat area, dissolved oxygen, depth and water temperature explained 85% of surface pCO 2 variation. Levels of pCO 2 varied with inundation extent, with higher pCO 2 values occurring in periods with greater water depth and inundation area, and lower dissolved oxygen concentrations and water temperatures. In a separate analysis for the Amazon-Solimões river and floodplains, ecosystem type (lotic or lentic), hydrological period, water temperature, dissolved oxygen, depth and dissolved phosphorus explained 83% of pCO 2 variation. Our results demonstrate the influence of alluvial floodplains and seasonal variations in their limnological characteristics on the pCO 2 levels in river channels of the lowland Amazon. © 2019, Springer Nature Switzerland AG.